2014
DOI: 10.1007/s12013-014-0121-3
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Extracorporeal Membrane Oxygenation Alleviates Intestinal Ischemia–Reperfusion Injury in Prolonged Hemorrhagic Shock Animal Model

Abstract: Intestinal ischemia-reperfusion injury is one of the main factors leading to multiple organ failure after resuscitation of prolonged hemorrhagic shock; however, the current conventional fluid resuscitation still cannot effectively reduce intestinal injury caused by prolonged hemorrhagic shock. To investigate the effect of ECMO resuscitation on alleviating intestinal ischemia-reperfusion injury in a prolonged hemorrhagic shock rabbit model. Thirty New Zealand white rabbits were randomly divided into three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…These complications will result in shock, hemorrhage, thrombosis, and hemolysis Ogaki et al, 2014). Therefore, various means should be employed in the treatment of HS, such as ensuring airway ventilation, providing endotracheal intubation and mechanical ventilation, and conducting immediate hemostasis (Ogaki et al, 2014;Zhao et al, 2014). Adiponectin (ADPN) has a pronounced effect on vascular endothelial function; thus, much attention has and should be paid to the relationship between ADPN and HS (Lim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These complications will result in shock, hemorrhage, thrombosis, and hemolysis Ogaki et al, 2014). Therefore, various means should be employed in the treatment of HS, such as ensuring airway ventilation, providing endotracheal intubation and mechanical ventilation, and conducting immediate hemostasis (Ogaki et al, 2014;Zhao et al, 2014). Adiponectin (ADPN) has a pronounced effect on vascular endothelial function; thus, much attention has and should be paid to the relationship between ADPN and HS (Lim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In previous experimental I/R model, the observation of intestinal viability loss was usually limited to longterm ischemia (3 hours after injury) [36,37] . After ischemic injury, the study of monitoring intestinal permeability in vitro showed that it took at least 60 minutes to detect the change of intestinal barrier function, which could not quickly judge the change of intestinal viability [3] .…”
Section: Discussionmentioning
confidence: 99%
“…During hemorrhagic shock, increased levels of ICAM-1 induce s adhesion and activation of inflammatory cells, which is a key indicator of uncontrolled inflammatory responses and organ dysfunction (32). Interference with ICAM-1 may be beneficial for regaining and/or maintaining the balance of inflammation and organ function (32)(33)(34). In the current study, ICAM-1 was increased in plasma, and TNF-α was increased in plasma, lung, kidney, liver and myocardium samples following PHSML injection, suggesting that tissue injury was caused by ICAM-1-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%